Elaboration of cookies using with chichá almonds (Sterculia striata Naud.) and gurguéia nuts (Dipteryx lacunifera Ducke) (Research, Society and Development, 2022)
The aim of this work was to develop cookies using with chichá almonds and gurguéia nut and verify their acceptance. Two formulations of cookies were developed, in formulation A the chichá almond was used and, in the B, the gurguéia nut. Sensory analysis was performed by 105 untrained assessors aged between 18 and 45 years old. In order to verify the acceptance of the elaborated product, the nine-point hedonic scale was used, to evaluate the intention to purchase a test with a five-point scale was applied and to determine the preferred sample a paired test of preference was used. By the hedonic scale test the sensorial acceptance was 89% for formulation A and 91% for B. In the purchase intention test, 67.5% of the advisors would buy formulation A and 70.5% would buy B, the two cookies being equally accepted, as there was no statistically significant difference between the two cookies formulations, in both tests. However, as for the preference, the cookie containing chichá almonds in its formulation was preferred among the advisors. Thus, the enrichment with chichá almond and gurguéia nut in the development of cookies is a viable option, since the elaborated cookies presented an excellent sensorial acceptance.